Uncaria gambier -a New Source of Katha - Soni, P. L.; Sharma, H. W. (Indian Forester, 2001)
Katha manufacturing in India is an important forest based chemical industry which enables economical upliftment of both rural and urban people. Uncaria gambier Roxb. is cultivated in Malaysian countries for the production of gambier used for tanning leather. Gambier is very much similar to Cutch or dark catechu obtained from A.catechu. Gambier maintains its importance as a masticatory in South East Asia and less as a tanning material. There are no adverse reports available against the use of gambier for human consumption. Process for the preparation of Katha from U. gambier extract having more catechins and yield with less, insolubles and heavy metals than A. catechu is reported. Product was evaluated for oral and oral mucosa toxicity and found non-toxic. Physico-chemical characteristic of gambier Katha is better than Khair Katha.